Towards a Sharīʿah-Compliant Framework for AI-Supported Fatwa in Malaysian Hajj Management: A Maqāṣid al-Sharīʿah and Governance Perspective - Ab Razak, Mohamed Rashid Bin; Drs Nasrul, Muhammad Amrullah Bin; Abbas, Ibrahim (Millah: Journal of Religious Studies, 2026)
Malaysia’s Hajj management system is widely recognized for integrating financial, logistical, and religious services through a centralized institutional framework. As interest grows in using Artificial Intelligence to provide real-time religious guidance, important questions arise regarding the permissibility, reliability, and governance of AI-supported fatwa delivery. This article aims to develop a Sharīʿah-compliant framework for AI-supported fatwa in Malaysian Hajj management that aligns with maqāṣid al-sharīʿah and existing fatwa governance structures. Using a qualitative doctrinal methodology, the study analyzes principles of uṣūl al-fiqh, Malaysian legal and institutional arrangements governing fatwa issuance, Hajj-related resolutions, and contemporary scholarship on Artificial Intelligence governance and accountability. The analysis identifies key requirements for valid fatwa delivery, including scholarly competence, evidentiary reasoning, contextual awareness, and adherence to state-based authority. It further highlights recurring Hajj issues involving ritual errors, compensatory sacrifices, health concessions, women’s rulings, and travel constraints that may benefit from timely digital assistance. While Artificial Intelligence offers advantages such as rapid access, multilingual support, and personalized guidance, significant risks remain, including hallucinated rulings, jurisdictional confusion, and diminished scholarly accountability. To address these challenges, the study proposes a hybrid framework based on curated and authenticated fatwa corpora, Retrieval-Augmented Generation, authority tagging, embedded evidentiary reasoning, escalation protocols to accredited muftis, and institutional audit mechanisms. Guided by the protection of religion, life, intellect, dignity, and wealth, the framework positions Artificial Intelligence as a supportive rather than substitutive tool. The study concludes that AI-supported fatwa delivery is normatively defensible only when firmly anchored to state authority, robust governance safeguards, and the ethical objectives of Sharīʿah, providing a practical blueprint for responsible innovation in Hajj management.